Features of Cytological Profile of Induced Sputum in School-Age Children with Exercise-Induced Bronchial Asthma - L.O. Bezrukov; Ye.P. Ortemenka (Zaslavsky O.Yu., 2016)
On the basis of Regional children's clinical hospital of Chernivtsi, in 41 school-age children with persistent bronchial asthma (BA), the nature of airways inflammation has been studied with the aim of differential choice of anti-inflammatory basic therapy. The first (I) clinical group consisted of 22 children with exercise-induced BA phenotype, and the other 19 patients without a phenotype of exercise-induced BA were included in the second (II) clinical group. Cytological analysis of induced sputum was conducted by I.D. Pavord method (1996). Patients with exercise-induced BA are characterized by hypogranulocytic inflammation of the airways, with a predominance of eosinophil-mediated reactions associated with hyperlymphocytic infiltration of the bronchi. So, bronchial eosinophilia (≥ 2 % of eosinophils in the sputum) was registered in 81.8 % of pupils in group I and in 63.2 % - in group II (Pϕ > 0.05). Meanwhile, hyperlymphocytic (number of lymphocytes in the cellular sediment of the sputum ≥ 11 %) inflammatory response of the airways was recorded twice as often in patients with exercise-induced BA (22.7 % of children) compared to group II patients (10.5 %) (Pϕ > 0.05). In patients without exercise-induced BA phenotype, a significant neutrophilic inflammatory response of the airways (relative content of neutrophils in the induced sputum ≥ 69 %) was three times more likely (36.8 % of cases) in comparison with patients from the I clinical group (13.6 %) (Pϕ < 0.05). At the same time, the neutrophilic type of the airway inflammatory response was associated with a significant damage of the bronchial mucosa, which manifested by an increase in the number (≥ 40 % of the cylindrical epithelial cells in the induced sputum) of desquamated epithelium in this cohort of patients (68.4 %) compared to group I (40.9 % of children; Pϕ < 0.05).